Efektivitas Model Kooperatif Tipe Two Stay Two Stray dan Think Pair Share dalam Meningkatkan Kecakapan Sosial Siswa Materi Sistem Reproduksi - Farisah Ainina Harahap; Hasruddin; Ely Djulia (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to examine the effectiveness of the Two Stay Two Stay (TSTS), Think Pair Share (TPS), and Conventional cooperative learning models in improving students' social skills in human reproduction. This study is quantitative in nature and quasi-experimental in design. The research design is a Posttest-Only Control Group Design. The population in this study was 156 students in grade IX MTsN 3 Padangawas, and the sample in this study was 78 people. Sampling was conducted using cluster random sampling, and the research sample consisted of 3 classes, namely TSTS, TPS, and Conventional classes. The data collection technique in this study used a questionnaire instrument. Data analysis used the Kruskal Wallis test. The results of the data analysis showed that the Asymp sig value was 0.000, indicating that there was a significant effect between the groups using the TSTS, TPS, and control (conventional learning) models on students' social skills. The mean rank of the TPS group was 51.06, followed by the TSTS group at 48.48, and the Conventional group at 18.96. This indicates that the TPS learning model has the most effective social skills value compared to the TSTS and Conventional groups.